2020
DOI: 10.14254/2071-8330.2020/13-3/7
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering trade and investment-led growth hypothesis: New evidence from Nigerian economy

Abstract: The need to revisit the trade and investment-led growth hypothesis in the case of Nigerian economy has become pertinent following the recent record drop of 15% in FDI inflows to West Africa. This fall in FDI flow to the region has been primarily attributed to the abysmal performance of Nigeria in attracting FDI as the largest economy in the sub-region despite an average rise in the rate of FDI flow to Africa as a continent at large. In this study, the trade and foreign direct investment-led growth hypothesis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Accordingly, hi-tech exports are crucial for technical advancement in E7 countries. Nevertheless, the findings suggest that higher levels of gross domestic product are correlated with greater innovation in E7 economies which affirms the findings of Coban et al (2020), Gyamfi et al (2021), and Bekun et al (2021). Because of the economic production efficiency, GDP coefficient is strong and significant in the short term and in the long term.…”
Section: Resultssupporting
confidence: 77%
“…Accordingly, hi-tech exports are crucial for technical advancement in E7 countries. Nevertheless, the findings suggest that higher levels of gross domestic product are correlated with greater innovation in E7 economies which affirms the findings of Coban et al (2020), Gyamfi et al (2021), and Bekun et al (2021). Because of the economic production efficiency, GDP coefficient is strong and significant in the short term and in the long term.…”
Section: Resultssupporting
confidence: 77%
“…In conclusion, foreign capital can be beneficial for the SSA countries’ infrastructures development if inflows are channeled to developmental projects and are managed wisely but FDI inflow into some parts of the SSA region has been described to be abysmal (Çoban et al, 2020). Hence, the governments need to do more on designing strategies to attract FDI in developmental projects, while doing so, regulations that aid in the efficient management of foreign capital are also required.…”
Section: Conclusion and Policy Recommendationmentioning
confidence: 99%
“…The panel causality test is necessitated by the need to assess the Granger non-causality movement from the explanatory variables to the explained variable given a heterogeneous panel dataset. Following the importance of testing for causality in empirical studies (Balsalobre-Lorente & Leitão, 2020;Onifade, Çevik, et al, 2020;Roudi et al, 2019;Çoban et al, 2020;Bekun et al, 2019;Taiwo et al, 2020;Onifade, Ay, et al, 2020), we report the causality test results for this study in Table 8. From the table, it can be observed that there is a feedback causality between three variables and the dependent variable, namely, airline transport and economic growth, globalization and growth, and also between urbanization and growth.…”
Section: Dumitrescu and Hurlin Causality Testmentioning
confidence: 99%